Restorative Justice in ITE Law Enforcement: Alternative Solutions to Digital Sengeketa in Indonesia - Firdausi, Ulya Shafa; Febriansyah, Ferry Irawan; Ramadhan, Azis Akbar (Faculty of Law, Universitas Muhammadiyah Pontianak, 2026)
The purpose of this study is to explore alternative approaches to resolving digital disputes in Indonesia. The rapid advancement of digital technology has led to increased interaction within cyberspace, but has also given rise to new forms of conflict addressed through the Law on Electronic Information and Transactions (ITE Law). Law enforcement related to violations of the ITE, particularly in minor cases such as online defamation, the spread of hoaxes, or small-scale online fraud-often results in disproportionate criminalization. Such a repressive legal approach is considered ineffective and fails to reflect substantive justice. This study examines the potential of restorative justice as a more humane, recovery-oriented alternative for resolving digital disputes. Using a normative juridical approach, the research analyzes the relevance of restorative justice principles within the context of the ITE Law and assesses the readiness of Indonesian regulations and law enforcement institutions to implement them. The findings indicate that many digital offenses are complaint-based (delik aduan) and can be resolved outside the courtroom if the parties involved demonstrate goodwill. Therefore, integrating restorative justice into the enforcement of the ITE Law is a crucial step toward achieving more inclusive, efficient, and socially restorative justice.